Unitary and dualistic aspects of anthropology by Thomas Aquinas in relation to a human being as imago dei - Slováček, Petr (Hybris, 2020)
The present text deals with two layers of philosophic psychology/anthropology in the works of Thomas Aquinas and strives to examine the mutual relationships and interrelated meanings between these layers while paying particular attention to the biblical image of a human being as imago Dei. With respect to this aim, the paper contains a justification of the distinction between philosophic psychology, which understands soul as a substantial form of the human being, and dualistic philosophic psychology, which views soul as the subject of activities, or as incomplete substance. This distinction is then confirmed as confronted with the way Thomas Aquinas delimits the human being as imago Dei in his Summa Theologiae, by which means the way we understand this expression becomes more exact, and the importance of Thomas's dualistic terminology, which we encounter in his works, is emphasised at the same time.